Structure – Function relationship of Australian Acacia seed protein concentrates: Amino acid composition, in vitro protein digestibility and molecular properties. (February 2023) - Adiamo, Oladipupo Q.; Netzel, Michael E.; Hoffman, Louwrens C.; Gidley, Michael J.; Osborne, Simone; Sultanbawa, Yasmina
Abstract: The nutritional, functional, in vitro protein digestibility (PD), structural, and molecular properties of Acacia seed protein concentrates (ASPC) from three Acacia species ( Acacia victoriae, A. coriacea and A. cowleana ) were investigated and compared with a commercial soy protein isolate (SPI). The essential amino acid profile in ASPC, except for methionine, exceeded the minimum daily requirements for adults recommended by the FAO/WHO. The ASPC PD, particularly from A. victoriae and A. coriacea, was considerably high (64.2–79.3%), but lower than SPI (89.5%). ASPC proteins had higher molecular weights ranging from 50 to 65 kDa (associated with 7S vicilin subunit), better protein solubility and oil absorption capacity than SPI. Emulsifying properties were comparable between ASPC and SPI. Among the Acacia species, the proteins from A. victoriae and A. cowleana exhibited higher protein quality, foaming capacity and solubility compared to A. coriacea . Overall, ASPC from A. victoriae and A. cowleana showed potential as ingredients in food processing.